2020
DOI: 10.1111/1365-2435.13540
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage to lipids is rapidly reduced during migratory stopovers

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. Abstract 1. Most migrating birds need to stopover in between flights in order to refuel. Lately, additional purposes of stopover have been suggested, including physiological recovery from metabolically demanding migratory flight. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 63 publications
0
35
0
Order By: Relevance
“…Within-individual changes can reveal important information about the range and capacity of responses across time and contexts. Although oxidative damage is not directly a physiological response, but an outcome, it was recently shown that even oxidative damage to lipids can vary rapidly within an individual (Eikenaar et al, 2020). Thus, it would be highly valuable to also view oxidative damage as a variable trait, and to explore patterns of clearance and regeneration of oxidative damage over time to establish when it actually becomes a threat to fitness.…”
Section: Physiological Plasticity: Chronic and Acute Responsesmentioning
confidence: 99%
“…Within-individual changes can reveal important information about the range and capacity of responses across time and contexts. Although oxidative damage is not directly a physiological response, but an outcome, it was recently shown that even oxidative damage to lipids can vary rapidly within an individual (Eikenaar et al, 2020). Thus, it would be highly valuable to also view oxidative damage as a variable trait, and to explore patterns of clearance and regeneration of oxidative damage over time to establish when it actually becomes a threat to fitness.…”
Section: Physiological Plasticity: Chronic and Acute Responsesmentioning
confidence: 99%
“…Relating detailed knowledge of the birds' intrinsic condition, e.g. energy stores [7], age [65,66], sex [67], migratory destination [21], physiology [5,6] and immune system [68], to the departure decision may eventually allow formulating distinct conditions at which "most" individuals decide to resume migration or to remain at stopover. Such an approach neglects the migratory history of the birds before they entered the stopover site and their future expectations of better or worse conditions elsewhere [48,69] which differ between individuals.…”
Section: Resultsmentioning
confidence: 99%
“…This could be a signal in the decision-making process to remain at this more favourable stopover [41], as the exploitation of higher energy accumulation rates than before would be tantamount to an increase in the migration speed [48,49,56]. Alternatively, these long-staying redstarts might need longer to physiologically recover from the previous energetically demanding migratory flight than the others [5]. Regarding the potential influence of the weather on the departure decision, temperature, air pressure, precipitation and wind conditions (Additional file 1: Figure S1) did not deteriorate during the 5 days after the day of capture (Additional file 1).…”
Section: Night-to-night Departure Decisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many individual migrants, however, do not arrive at stopover with fully depleted fuel stores, and fuelling is not the only reason why migrants land at a stopover site. Migrants may land, for example, to avoid flying during the day (Alerstam 2009) or in inclement weather (Shamoun-Baranes et al 2017), to reduce the amount of oxidative damage incurred during flying (Eikenaar et al 2020), or because they need to compensate for sleep loss as a consequence of nocturnal flight (Ferretti et al 2019). For those migrants carrying enough fuel to support the next flight, the effect that fuel stores may exert on the motivation to depart from stopover may not be as clear cut as it is for lean individuals.…”
Section: Introductionmentioning
confidence: 99%